Polymorphisms in biotransformation and DNA repair genes, and survival on head and neck squamous cell carcinoma - Novais, Pedro Amorim; Bezerra, Débora Diniz; Barbosa, Ana Angélica Leal; Marques, Cintia Rodrigues; Ferreira, Marcílio, Filho; Rios-Santos, Fabrício; Magalhães da-Silva, Thiago (Brazilian Journal of Oncology, 2021)
Objective:This study analyzed the association between xenobiotic metabolism and DNA repair gene polymorphisms and overall survival (OS) and disease-free survival (DFS) in patients diagnosed with HNSCC in a Brazilian population. Methods: Retrospective study included 91 patients with a confirmed diagnosis of HNSCC. A total of 7 genes were analyzed: XRCC1, HOGG1, CYP1A1, GSTM1, GSTT1, GSTP1 and NAT2. Results: Regarding OS, the largest mean differences were observed comparing GSTT1 rs71748309 null and GSTT1 rs71748309 non-null genotypes (p=0.050). In the gene-gene interaction analysis, the higher difference to OS was observed to the combined genotypes of the GSTM1 rs4025935 and GSTT1 rs71748309 (p=0.286). Regarding DFS, the largest mean differences were observed comparing GSTT1 rs71748309 null and GSTT1 rs71748309 non-null genotypes (p=0.060) and to the combined genotypes of the GSTM1 rs4025935 and GSTT1 rs71748309 (p=0.313). Conclusion: None of the polymorphisms evaluated in xenobiotic metabolism or DNA repair genes were significantly associated with HNSCC survival in our population. Confirmation of these results in larger studies is required.
Keywords: Squamous cell carcinoma of head and neck; Survival; Polymorphism; Genetic; DNA; Gene.